Strategi Media Alternatif Proyek Multatuli dalam Menjaga Keberlangsungannya - Muhammad Afriski Nanda Pradana; Eni Maryani; Sri Seti Indriani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This research aims to provide an in-depth analysis of Project Multatuli as an alternative media outlet, focusing on both organizational and editorial perspectives. It also explores the challenges faced by such alternative media organizations. The findings reveal that Project Multatuli, at a fundamental level, can be regarded as critical alternative media that meets the criteria outlined by Sandoval and Fuchs. As an alternative media outlet, Project Multatuli relies on funding from donors, grants, and initiatives from